2012
DOI: 10.1016/j.jinf.2012.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Haemophilus influenzae in the United States, 1999–2008: Epidemiology and outcomes

Abstract: Summary In a multivariable analysis of cases with invasive H. influenzae, prematurity in infants, advanced age and certain chronic diseases in adults were associated with an increased risk of in-hospital death. Nontypeable disease was associated with higher mortality in the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 23 publications
4
26
0
1
Order By: Relevance
“…[5][6][7][8][9][10][11][12] Although 65% of the cases described in the present review were not serotyped, 6 cases for which this information was available revealed that 4 cases (67%) were NTHi and 2 (33%) were Hib. Thus, our findings reiterate the importance of NTHi as a cause of H influenzae bacteremia.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…[5][6][7][8][9][10][11][12] Although 65% of the cases described in the present review were not serotyped, 6 cases for which this information was available revealed that 4 cases (67%) were NTHi and 2 (33%) were Hib. Thus, our findings reiterate the importance of NTHi as a cause of H influenzae bacteremia.…”
Section: Discussionmentioning
confidence: 59%
“…21 It is also worth noting that H influenzae infections are common at both extremes of age. 5,11 In addition to the changes in the serotype distribution of H influenzae infections, widespread childhood immunization has shifted the trend of infection toward elderly persons with comorbidities. 5,6,11,12,17,21 Common factors include cancers and other immunocompromised states, and this is especially true where humoral immunity is compromised.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pneumonia was reported across all serotypes. Clinical presentation is known to be associated with different serotypes and strongly related to age (50,51) although these results must be interpreted with caution as data on clinical presentation was missing for 54.4% of cases.…”
Section: Invasive Haem Ophilus Influenzae Diseasementioning
confidence: 85%
“…Before introduction of the Hib vaccine, Hib was responsible for about 20,000 cases of and about 1,000 deaths from severe disease in children annually, but invasive Hib disease has nearly been eradicated since the introduction of the Hib conjugate vaccine (379). Other strains of H. influenzae, particularly noncapsular (nontypeable) strains, remain important pathogens in humans worldwide (379)(380)(381).…”
Section: Human Diseases Caused By Other Pasteurellaceaementioning
confidence: 99%